Phenotypic Effects of Wild-Type and Mutant SOD1 Expression in N9 Murine Microglia at Steady State, Inflammatory and Immunomodulatory Conditions - Vaz, Ana Rita; Pinto, Sara; Ezequiel, Catarina; Cunha, Carolina; Carvalho, Luís A.; Moreira, Rui; Brites, Dora (Frontiers in Cellular Neuroscience, 2019)
Accumulation of mutated superoxide dismutase 1 (mSOD1) in Amyotrophic Lateral Sclerosis (ALS) involves injury to motor neurons (MN), activation of glial cells and immune unbalance. However, neuroinflammation, besides its detrimental effects, also plays beneficial roles in ALS pathophysiology. Therefore, the targeting of microglia to modulate the release of inflammatory neurotoxic mediators and their exosomal dissemination, while strengthening cell neuroprotective properties has gained growing interest. We used the N9 microglia cell line to identify phenotype diversity upon the overexpression of wild-type (hSOD1WT) and mutated G93A (hSOD1G93A) protein. To investigate how each transduced cell respond to an inflammatory stimulus, N9 microglia were treated with lipopolysaccharide (LPS). Glycoursodeoxycholic acid (GUDCA) and dipeptidyl vinyl sulfone (VS), known to exert neuroprotective properties, were tested for their immunoregulatory properties. Reduced FiZZ1, IL-10 and TLR4 mRNAs were observed in both transduced cells. However, in contrast with hSOD1WT-induced decreased inflammatory markers, microglia transduced with hSOD1G93A showed upregulation of pro-inflammatory (TNF-α/IL-1β/HMGB1/S100B/iNOS) and membrane receptors (MFG-E8/RAGE). Importantly, their derived exosomes were enriched in HMGB1 and SOD1. When inflammatory-associated miRNAs were evaluated, increased miR-146a in cells with overexpressed hSOD1WT was not recapitulated in their exosomes, whereas hSOD1G93A triggered elevated exosomal miR-155/miR-146a, but no changes in cells. LPS stimulus increased M1/M2 associated markers in the naïve microglia, including MFG-E8 and miR-155 and miR-146a, which expression was decreased in both hSOD1WT and hSOD1G93A cells treated with LPS. Treatment with GUDCA or VS decreased TNF-α, IL-1β, HMGB1 and S100B in hSOD1G93A microglia, as well as miR-155 upregulation. Only GUDCA was able to increase cellular IL-10, RAGE and TLR4, as well as cellular miR-21, while decreasing exosomal miR-155 cargo. Conversely, VS reduced MMP-2/MMP-9 activation, as well as upregulated MFG-E8 and miR-146a, while producing miR-21 shuttling into exosomes. The current study supports the powerful role of overexpressed hSOD1WT in attenuating M1/M2 activation, and that of hSOD1G93A in switching microglia from the steady state into a reactive phenotype with low responsiveness to stimuli. This work further reveals GUDCA and VS as promising modulators of microglia immune response by eliciting common and compound specific molecular mechanisms that may promote neuroregeneration.